The Clinical significance of serum synaptophysin like 1 protein levels in breast cancer: SYLP-1 and breast cancer - Uzun, Hafize; Kosem, Yagmur Ozge Turac; Velidedeoglu, Mehmet; Kocael , Pınar; Dumur , Seyma; Simsek , Osman (Journal of Medical Biochemistry, 2023)
Background: Mammography, used for breast cancer (BC) screening, has limitations such as decreased sensitivity in dense breasts. Currently used tumor markers are insufficient in diagnosing breast cancer. In this study, we aimed to investigate the relationship between serum levels of synaptophysin-like protein 1 (SYPL1) and BC, as well as compare SYPL1 with other blood tumor markers. Method: The study group consisted of 80 female patients with a histopathological diagnosis of invasive BC and didn’t receive any radiotherapy/chemotherapy. The control group 72 women with noprevious history of breast disease and evaluated as Breast Imaging Reporting and Data Systems (BI-RADS 1-2) on imaging. Serum SYPL1, cancer antigen 15-3 (CA 15-3) and carcinoembryonic antigen (CEA) were measured in both groups. Results: The diagnostic values of SYPL1, CEA and CA15-3 proteins in diagnosing BC were statistically significant. The sensitivity of SYPL1 was 48.75%, with a specificity of 80.56%. CA15-3 had a sensitivity of 80% and a specificity of 49.30%. There wasn’t statistically significant correlation between serum SYPL1 and tumor diameter, lymph node metastasis, distant organ metastasis, and stage. Conclusion: The serum SYPL1 maintained a higher discriminatory ability for BC. The serum SYPL1 level can be used with high specificity in the diagnosis of BC. Although SYPL1 has low diagnostic value in BC by itself.
Keywords: Synaptophysin-like 1, breast cancer, dense breasts, tumor markers